Energy Efficient Tag Identification Algorithms For RFID: Survey, Motivation And New Design - Su, Jian; Sheng, Zhengguo; Leung, Victor C. M.; Chen, Yongrui (IEEE wireless communications, 2019)
RFID is widely applied in massive tag based applications, thus effective anti-collision algorithms to reduce communication overhead are of great importance to RFID in achieving energy and time efficiency. Existing MAC algorithms are primarily focusing on improving system throughput or reducing total identification time. However, with the advancement of embedded systems and mobile applications, the energy consumption aspect is increasingly important and should be considered in the new design. In this article, we start with a comprehensive review and analysis of the stateof- the-art anti-collision algorithms. Based on our existing works, we further discuss a novel design of anti-collision algorithm and show its effectiveness in achieving energy efficiency for the RFID system using EPCglobal C1 Gen2 UHF standard.